Digital Payment Innovation in Islamic Boarding Schools: Transforming Culture, Efficiency, and Accountability - Mahmudi, Rois; Khotib, Ahmad; Ningsih, Lely Ana Ferawati Eka (Ahlussunnah: Journal of Islamic Education, 2026)
This study explores digital payment innovation and its role in transforming organizational culture in Islamic boarding schools. Using a qualitative case study approach within an Indonesian Islamic boarding school context, data were collected through in-depth interviews, participant observation, and documentation. Data validity was ensured through triangulation of sources, methods, and observers. The findings reveal that digital payment innovation reshapes administrative interaction patterns, creating a trade-off between increased work efficiency and reduced intensity of direct personal interactions previously inherent in cash-based transactions. At the same time, digitalization strengthens transparency and accountability through the creation of a structured digital audit trail. The implementation of digital fund reporting systems enables real-time monitoring of transactions by students’ guardians, shifting the basis of trust from personal relationships to data-driven accountability. Furthermore, staff roles evolve from manual administrative tasks toward more strategic functions, fostering a more efficient, accountable, and data-driven organizational culture. This study contributes by proposing a technology tradition harmonization model as a strategic framework for cultural transformation in Islamic boarding schools in the digital era.